Assembly encapsulation of BSA and CCCH-ZAP in the sodium alginate/atractylodis macrocephalae system. Issue 20 (26th April 2022) - Zhang, Shuxin; Fan, Hai; Yi, Chunrong; Li, Ying; Yang, Kunmei; Liu, Shenglong; Cheng, Ziqiang; Sun, Jianchao
Abstract : ZAP and BSA can be encapsulated in the sodium alginate/atractylodis macrocephalae system using an assembly method. Abstract : Zinc finger antiviral proteins (ZAP) can significantly inhibit the replication of avian leukosis virus subgroup J (ALV-J), but the traditional method of ZAP administration is by injection, which can easily cause stress effects in chickens. In this work, we established a sodium alginate/atractylodis macrocephalae system for the encapsulation of CCCH-type zinc finger antiviral protein (CCCH-ZAP). Because of the high cost of ZAP, we first chose bovine serum albumin (BSA) as a model protein to investigate the encapsulation performance. The SEM images clearly confirmed that BSA and the sodium alginate/atractylodis macrocephalae system can assemble easily to form relatively stable nanostructures, and the encapsulation amount of BSA can reach 68%. Subsequently, the encapsulation of ZAP was studied. The SEM and the encapsulation experiments confirmed that ZAP can also be assembly encapsulated in the sodium alginate/atractylodis macrocephalae system with the encapsulation amount of 80%. Release studies showed that the SA/AM-ZAP nanocomposite was able to achieve a release rate of 32% of ZAP. This work successfully confirms the assembly encapsulation of ZAP, which will be beneficial for the usage of ZAP-based animal drugs.